Clinico mycological study of dermatophytosis - Janardhan, B.; Vani, G. (International Journal of Research in Medical Sciences, 2016)
Background: Dermatophytoses is common, more prevalent in tropical and subtropical countries including India. Though not life threatening as it can cause great discomfort particularly in immunosuppressive conditions. It remains a general public health problem, which is prevalent in all age groups and both sexes. Aims: To study clinicomycological profile of patients. Methods: The Cross Sectional study was done on clinically diagnosed cases of Dermatophytosis with sample size of 200 cases for one and half year period. Results: The males to female ratio are 1.86:1. The common age group affected was 31-40years. Dermatophytosis was common in active workers, more common in urban than rural population particularly in low socioeconomic group of people and in summer season. Tinea corporis was the common clinical variant. 133 cases were both KOH and culture positive. The KOH mount was positive in 90% cases. In the present study 144 patients (72%) had positive culture results and 47 cases were KOH positive but culture negative, 11 cases were culture positive but KOH negative and 9 cases were both KOH and culture negative. Microsporum audoinii was isolated in 2%, Trichophyton mentagrophytes in 14%, Trichophyton rubrum in 52% and Trichophyton violaceum in 4%. Conclusions: Tinea corporis and Tinea cruris were the most common clinical types. Tinea corporis was predominantly a disease of adult males whereas Tinea capitis was seen mainly in pre- pubertal age group. Potassium hydroxide (KOH) wet mount and cultures were done for all the cases. T. rubrum was the commonest species isolated from most clinical types followed by T. mentagrophytes except T. capitis where T. violaceum was isolated.